ATP1A3 mutation in rapid-onset dystonia parkinsonism: New data and genotype-phenotype correlation analysis - Yu, Lihua; Peng, Guoping; Yuan, Yuan; Tang, Min; Liu, Ping; Liu, Xiaoyan; Ni, Jie; Li, Yi; Ji, Caihong; Fan, Ziqi; Zhu, Wenli; Luo, Benyan; et al. (Frontiers in Aging Neuroscience, 2022)
Background Rapid-onset dystonia parkinsonism (RDP) is a rare disease caused by ATP1A3 mutation with considerable clinical heterogeneity. Increased knowledge of RDP could be beneficial in its early diagnosis and treatment. Objective This study aimed to summarize the gene mutation spectrum of ATP1A3 associated with RDP, and to explore the correlation of ATP1A3 variants with RDP clinical phenotypes. Methods In this study, we reported two RDP patients from a family with a novel inherited ATP1A3 variant. Then, we reviewed and analyzed the available literature in English focused on ATP1A3-causative RDP. A total of 35 articles covering 15 families (59 patients) and 36 sporadic RDP cases were included in our analysis. Results The variant A813V (2438C>T) in ATP1A3 found in our cases was a novel mutant. Delays in diagnosis were common, with a mean delay time of 14 years. ATP1A3 had distinct RDP-related mutation hotspots, which consisted of exon8, 14, 17, and 18, and the most frequently occurring variants were T613M and I578S. Approximately 74.5% of patients have specific triggers before disease onset, and 82.1% of RDPs have stable symptoms within 1 month. The incidence rates of dystonia and bradykinesia are 100 and 88.1%, respectively. The onset site varied and exhibited a rostrocaudal gradient distribution pattern in 45% of patients with RDP. Approximately 63.6% of patients had mild improvement after receiving comprehensive interventions, especially in gait disturbance amelioration. Conclusion In patients with acute and unexplained dystonia or bradykinesia, gene screening on ATP1A3 should be timely performed. When a diagnosis has been made, treatments that may be effective are to be attempted. Our study would be helpful for the early diagnosis and treatment of ATP1T3-related RDP.